Clinical and laboratory predictors of therapeutic response to Tocilizumab in rheumatoid arthritis - GOREA, Marius; CIORESCU, Camelia; GROPPA, Liliana; CHIȘLARI, Lia; CAZAC, Victor; RUSSU, Eugeniu (One Health & Risk Management, 2025)
Introduction. Biological disease-modifying antirheumatic drugs (bDMARDs), such as tocilizumab (TCZ), are essential for reducing disease activity in moderate to severe rheumatoid arthritis (RA). This study aims to identify clinical and laboratory predictors of a favorable response to TCZ, enabling personalized therapeutic strategies. Material and methods. A longitudinal clinical study in dependent samples included 133 bio-naïve patients (121 women, 12 men, mean age 49.87±13.31 years) with seropositive RA (radiological stages I-III) treated with TCZ and csDMARDs at the Timofei Moșneaga Republican Clinical Hospital. Clinical and laboratory parameters were monitored monthly over a six-month period. Statistical analysis was performed using Spearman’s correlation and multiple regression. The Wilcoxon signed-rank test was applied to compare parameters before and after TCZ treatment. Results. Favorable response predictors included swollen joint counts (ρ=0.59, p<0.01), tender joint counts (ρ=0.40, p<0.01), C-reactive protein (ρ=0.46, p<0.01), ESR (ρ=0.25, p<0.01), platelet count (ρ=0.29, p<0.01), hemoglobin (ρ=-0.26, p<0.01), hematocrit (ρ=-0.23, p<0.01), and age (ρ=-0.49, p<0.01). Regression analysis confirmed the influence of swollen joint counts (ρ=0.30, p<0.001), age (ρ=-0.30, p<0.001), and C-reactive protein (ρ=0.18, p=0.016) on DAS28 reduction. Conclusions. Swollen and tender joint counts, C-reactive protein, and age are key independent predictors of therapeutic success with TCZ after six months of treatment.